2017
DOI: 10.3945/ajcn.116.143982
|View full text |Cite
|
Sign up to set email alerts
|

Learning to like vegetables during breastfeeding: a randomized clinical trial of lactating mothers and infants

Abstract: Background: What lactating mothers eat flavors breast milk and, in turn, modifies their infants' acceptance of similarly flavored foods. Objective: We sought to determine the effects of the timing and duration of eating a variety of vegetables during breastfeeding on the liking of vegetables in both members of the dyad. Design: We conducted a randomized controlled study of 97 motherinfant dyads. Lactating mothers drank vegetable, beet, celery, and carrot juices for 1 mo beginning at 0.5, 1.5, or 2.5 mo postpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 60 publications
2
64
0
4
Order By: Relevance
“…Another way of exposing children to the flavour of vegetables is during pregnancy and breastfeeding. There is evidence that the mothers' diet can influence their infants' taste preferences through exposure via their amniotic fluid during pregnancy and via breast milk during breastfeeding (Mennella, Daniels, & Reiter, 2017;Mennella, et al, 2001;Ventura, 2017). Also the higher variation of taste in maternal milk compared to formula-milk is believed to increase acceptance of novel foods (Mennella & Beauchamp, 1991).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Another way of exposing children to the flavour of vegetables is during pregnancy and breastfeeding. There is evidence that the mothers' diet can influence their infants' taste preferences through exposure via their amniotic fluid during pregnancy and via breast milk during breastfeeding (Mennella, Daniels, & Reiter, 2017;Mennella, et al, 2001;Ventura, 2017). Also the higher variation of taste in maternal milk compared to formula-milk is believed to increase acceptance of novel foods (Mennella & Beauchamp, 1991).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, much of the research has focused on very young babies or preschool-aged children, but little is known about the infant-toddler period, which may be the most critical window for shaping dietary preferences [8]. Previous research focused on the milk feeding period in infancy has demonstrated that this may be a sensitive period for the development of flavor preferences in both breastfed [14,15] and formula-fed [16][17][18] babies, but less is known about the impact of flavor exposure as a result of CF behaviors. There is also little research in U.S. populations, where CF feeding practices differ from other cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The more varied the mother's diet is during lactation, the more varied the flavor of her milk (Mennella, 2007); this could explain why children who were breastfed are less picky and more willing to try new foods as they grow compared with children who were fed formula (Galloway et al, 2003). A recent study showed that drinking carrot and broccoli juice during breastfeeding increased the infant's acceptance of carrot-flavored cereal several months later, but did not affect acceptance of broccoliflavored cereal (Mennella et al, 2017). Consistent with this is that duration of breastfeeding was shown to be a predictor of vegetable intake (de Wild et al, 2018).…”
Section: Introductionmentioning
confidence: 99%